A Multi-Tenant Platform for Web-Based Library Applications Using Extreme Programming Methods - Azhar, Muhamad Faqih; Munir, Sirojul; Imaduddin, Zaki (The Indonesian Journal of Computer Science, 2025)
This research aims to develop a web-based platform for book collection lending management with a multi-tenant concept using the Extreme Programming (XP) development method, which includes the frontend and backend parts. This platform is designed to support the needs of library units and book collectors, allowing each entity to operate independently in one system to improve operational efficiency and effectiveness. The Research and Development (R&D) approach used in this research includes the following stages of planning, designing, implementing, and testing within the XP method framework. The technology used to develop this web-based platform includes Golang for the backend and React TypeScript for the frontend, with PostgreSQL as the database. Data was collected through observation and literature studies, while system testing used the Black Box Testing method. This platform provides various main features, such as library or collector registration, book collection management, borrowing and returning processes, and transaction history recording. The study results showed that platform development was carried out in six iterations over three months with a sprint duration of two weeks, resulting in an average work speed per sprint of 13.6 points. The test results showed that all features functioned according to user needs without any functional errors, with a system success rate of 100%. Overall, this platform is stated to be of good quality, ready to operate, and expected to support the management of digital book collections effectively and efficiently.